Advanced Life Support in Obstetrics - Lisa Soldat (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
Multiple barriers to high quality maternity care have been identified in Indonesia. One barrier is the shortage of well-trained maternity care providers, particularly in remote and rural areas. Maternity care training programs do not consistently prepare their graduates to provide high quality care. Poor pre-service training may then be compounded by a lack of post-service supervision and inadequate multispecialty teamwork. Maternity care continuing education is an important means to reinforce and improve the skills needed to provide high quality maternity care. Programs that have been developed for low- to middle-income countries focus on providing culturally appropriate information to improve competency, communication and teamwork. Improvement in quality of care has been documented, showing a decrease in maternal morbidity and mortality. This trend is reflected in improvements in patient satisfaction and trust, and ultimately supports the tenets of patient-centered care.